Hubungan Tujuan Lulus Tepat Waktu Terhadap Self Regulated Learning (SRL) Pada Mahasiswa Fakultas Kedokteran Umum Universitas Malahayati Angkatan 2018 - Puji Lestari, Sri Maria; Triwahyuni, Tusy; Utari, Elitha Martharina; Nurjanah, Siti (ANFUSINA: Journal of Psychology, 2020)
SRL is an individual process to achieve goals or targets, by managing and improving themselves (Manab 2016). With the support of a good SRL can encourage success that occurs especially for adolescents in the process of growth and development, a good SRL can improve student / teen achievement (Jantz 2011). According to Zimmermen and Pons, SRL has three factors, personal, behavioral, and environmental. One of the main factors of personal factors is the goals. To determine the correlation between the goals of graduating on time and self regulated learning (SRL) among sophomores in medical faculty of Malahayati University.A quantitative research with analytic design and cross sectional design and samples were collected by using accidental sampling. Data were evaluated with SPSS. The total sample of 122 students with moderate on-time graduation goals were 116 respondents (95.1%) . The students with high SRL were 62 respondents (50.8%). Statistical analysis using the Pearson test showed a p-value of 0.018 with a correlation test of +0.214. The goals of graduating on time with self-regulated learning in sophomores of Medical Faculty of Malahayati University are correlated. With low correlation power and positive correlation direction, the higher the goal of graduating on time, the higher the SRL, the goal of graduating on time affects the SRL by 4, 6%.